The decision intelligence handbook : practical steps for evidence-based decisions in a complex world / L.Y. Pratt and N.E. Malcolm ; foreword by John Elkington. - Pratt, Lorien; Malcolm, N. E. (O'Reilly, 2023)
With this book, authors L. Y. Pratt and N. E. Malcolm address three widespread data-driven decision-making problems: How can decision makers use data and technology to ensure desired outcomes? How can technology teams communicate effectively with decision makers to maximize the return on their data and technology investments? How can organizational decision makers assess and improve their decisions over time?